Faktor-faktor yang mempengaruhi profitabilitas pada sektor pertambangan yang terdaftar di BEI - Wahyuningsih, Sri; Bawono, Andy Dwi Bayu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Profitability is an analysis of financial ratios used to measure the company's ability to earn profit. The purpose of this study was to determine and analyze the effect of Liquidity, Company Size, Independent Board of Commissioners, and Audit Committee, on profitability, either simultaneously or partially. The population in this study are mining sector companies listed on the Indonesia Stock Exchange for the period 2018-2020 (a total of 126 companies). By using a sampling technique (purposive sampling) obtained as many as 42 companies that will be used as research objects. The test method to see the effect of the independent variable on the dependent variable is the multiple linear regression analysis method. Based on the results of the research simultaneously, it is known that, Liquidity, Company Size, Independent Board of Commissioners, and Audit Committee, have a significant effect on the profitability of mining sector companies listed on the Indonesia Stock Exchange for the period 2018-2020. However, partially, only Company Size and Independent Board of Commissioners have an effect on company profitability, while Liquidity and the Audit Committee have no significant effect on profitability.